2018
DOI: 10.1016/j.neuropharm.2017.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Microglial-specific transcriptome changes following chronic alcohol consumption

Abstract: Microglia are fundamentally important immune cells within the central nervous system (CNS) that respond to environmental challenges to maintain normal physiological processes. Alterations in steady-state cellular function and over-activation of microglia can facilitate the initiation and progression of neuropathological conditions such as Alzheimer’s disease, Multiple Sclerosis, and Major Depressive Disorder. Alcohol consumption disrupts signaling pathways including both innate and adaptive immune responses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 58 publications
3
36
0
Order By: Relevance
“…Longer‐term models of 2‐bottle choice offer intermittent alcohol with alcohol‐free days in between. Studies after thirty days of alcohol (60 days total) have revealed significant changes in microglia and astrocyte gene expression with significantly up‐regulated microglial immune signaling (Erickson et al, ; McCarthy et al, ) and may be an interesting alternative model to investigate with inflammasome inhibition in order to achieve more significant inflammation. Indeed, these models may offer avenues to study expression of inflammasome components and other proinflammatory biochemical signals in the setting of alcohol and inhibitor treatments, measurements we were unable to assess in this current self‐administration paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Longer‐term models of 2‐bottle choice offer intermittent alcohol with alcohol‐free days in between. Studies after thirty days of alcohol (60 days total) have revealed significant changes in microglia and astrocyte gene expression with significantly up‐regulated microglial immune signaling (Erickson et al, ; McCarthy et al, ) and may be an interesting alternative model to investigate with inflammasome inhibition in order to achieve more significant inflammation. Indeed, these models may offer avenues to study expression of inflammasome components and other proinflammatory biochemical signals in the setting of alcohol and inhibitor treatments, measurements we were unable to assess in this current self‐administration paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes have been shown to play a vital role in microglia function [11,12,13]. Microglia are the primary immune cells within the central nervous system (CNS) that regulate inflammatory processes during infection or cellular damage [9,12,14]. Upon activation, microglia undergo complex morphological and functional transitions, which includes increased phagocytosis, motility, and cytokine secretion [9].…”
Section: Introductionmentioning
confidence: 99%
“…Microglia secrete exosomes due to stress stimulated by alcohol consumption. Alcohol consumption disrupts signaling pathways (i.e., innate and adaptive immune responses) that are necessary for CNS homeostasis [14]. As a small molecule, alcohol can easily cross membrane barriers and reach different parts of the body very quickly, which can lead to total body alteration.…”
Section: Introductionmentioning
confidence: 99%
“…Post-mortem brains from alcoholics contain microglia at all four stages but are enriched in hyper-ramified microglia suggesting that ethanol sensitizes these cells (see (Crews & Vetreno, 2016). Further studies have demonstrated that microglial responses vary according to the duration, dose and pattern of alcohol exposure (Henriques et al, 2018;McCarthy et al, 2018;Yang et al, 2014). Very large doses of alcohol (Crews, 2008;Peng et al, 2017;Zahr et al, 2010), repeated cycles of ethanol exposure (Marshall et al, 2016;Zhao et al, 2013) or prior ethanol exposure are known to produce elevated levels of serum cytokines as well as microglia activation and long lasting increases in neuroimmune gene induction suggesting microglia priming (Crews & Vetreno, 2016;Perry & Holmes, 2014;Zou & Crews, 2010).…”
Section: Introductionmentioning
confidence: 99%